(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
A 14-year-old boy, 3rd issue of consanguineous parents presented with a nodular swelling in the lateral and upper aspect of his left thigh with difficulty in walking. Considering a bone tumor, he had undergone two orthopedic surgeries. During surgery, chalky material came out and histopathology revealed deposition of calcium hydroxyapatite. Biochemically he had persistent hyperphosphatemia. Imaging revealed a dense calcification around the left greater trochanteric region. Interestingly, his vitamin C level was found low. Biochemical screening of family members also revealed hyperphosphatemia in one of his elder brothers. We diagnosed the case as hyperphosphatemic familial tumoral calcinosis. The patient was advised to take a phosphate-restricted diet, phosphate binder, and vitamin C. The ectopic deposition of calcium in the soft tissue around a joint may be mistaken as a tumor. Family history and biochemical findings can help to reach the diagnosis. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2023; 2 (1): 32-34